Spatial justice: reintegrating the High Court and bridging the political divide - Krom, Brad Evan (My University, 2011)
The social contract is the link connecting a nation and its people: An intertwining and ever present bond between man and state. An inherent divide exists in this contract - a gap between the political theory and the societies that it governs. Lying in the middle of this rift is architecture, a powerful connection between man and state. In bridging the political divide architecture can become more than building because it represents a nation, its people and its laws. It can be the stage from which a nation addresses its people and from where the people connect to their government. This communication and interaction between state and citizen through architecture creates a space of inclusion that bridges the political divide. It becomes democratic in nature: a spatial justice